Weathering of microplastics and interaction with other coexisting constituents in terrestrial and aquatic environments - Duan, Jiajun; Bolan, Nanthi; Li, Yang; Ding, Shiyuan; Atugoda, Thilakshani; Vithanage, Meththika; Sarkar, Binoy; Tsang, Daniel C.W.; Kirkham, M.B. (Water research (Oxford), 2021)
•Sources of microplastics (MPs) are usually linked to anthropogenic activities.•The weathering rate of MPs is usually lower in water than on land.•The chemical structure of MPs, oxygen and temperature, control MP weathering.•Surface modification of weathered MPs affects their environmental behavior.•MP weathering in soils and sediments needs further research. Weathering of microplastics (MPs, < 5 mm) in terrestrial and aquatic environments affects MP transport and distribution. This paper first summarizes the sources of MPs, including refuse in landfills, biowastes, plastic films, and wastewater discharge. Once MPs enter water and soil, they undergo different weathering processes. MPs can be converted into small molecules (e.g., oligomers and monomers), and may be completely mineralized under the action of free radicals or microorganisms. The rate and extent of weathering of MPs depend on their physicochemical properties and environmental conditions of the media to which they are exposed. In general, water dissipates heat better, and has a lower temperature, than land; thus, the weathering rate of MPs in the aquatic environment is slower than in the terrestrial environment. These weathering processes increase oxygen-containing functional groups and the specific surface area of MPs, which influence the sorption and aggregation that occur between weathered MPs and their co-existing constituents. More studies are needed to investigate the various weathering processes of diverse MPs under natural field conditions in soils, sediments, and aquatic environments, to understand the impact of weathered MPs in the environment. [Display omitted]